THE EFFECTIVENESS OF STEM AND RHIZOME EXTRACT OF KECOMBRANG (Etlingera elatior) AS A NATURAL PRESERVATIVE FOR TILAPIA (Oreochromis niloticus) MEAT - Hernanda, Tasya; Nurlaili, Nurlaili; Noviyanti, Putri; Syafira, Irmaina; Aprilia, Lisa; Rofiah, Is Nur Dwi; Darmayanti, Citra (Jurusan Kimia Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Mulawarman, 2023)
Tilapia contains protein and has a high nutritional content, including minerals, vitamins and unsaturated fats. However, this fish is easily damaged and rotten. This is caused by the activity of enzymes, microorganisms, or oxygen oxidation. Therefore, it is necessary to use preservatives so that the fish does not spoil or rot quickly. One of the potential natural preservatives is the kecombrang plant, especially the stems and rhizomes which contain bioactive substances. This plant has antibacterial properties that can help slow down the decline in fish quality. This study aims to determine the effectiveness of kecombrang stem and rhizome extract as a natural preservative in tilapia meat. The effectiveness of kecombrang stem and rhizome extracts was determined by soaking tilapia meat in kecombrang stem and rhizome extracts at various times of 0, 3, and 6 hours. The protein content of tilapia meat was measured by the biuret test. The results of this study indicated that the percentage of protein degradation inhibitors in kecombrang stem extract was 30.1% for 3 hours and 17.8% for 6 hours while in kecombrang rhizome extract was 34.2% for 3 hours and 22.6% for 6 hours. This shows that kecombrang rhizome extract is more effective as a natural preservative for tilapia meat compared to kecombrang stem extract. Keywords: Tilapia, kecombrang stem, kecombrang rhizome, natural preservative, biuret